National Survey and Community Advisory Board Development for a Bipolar Disorder Biobank. (20th August 2015) - Frye, Mark A; Doederlein, Allen; Koenig, Barbara; McElroy, Susan L; Nassan, Malik; Seymour, Lisa R; Biernacka, Joanna M; Daniels, Allen S
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study was to engage a national advocacy group and local stakeholders for guidance in developing a bipolar disorder biobank through a web‐based survey and a community advisory board. Methods The Depression and Bipolar Support Alliance and the Mayo Clinic Bipolar Biobank conducted a national web‐based survey inquiring about interest in participating in a biobank (i.e., giving DNA and clinical information). A community advisory board was convened to guide establishment of the biobank and identify key deliverables from the research project and for the community. Results Among 385 survey respondents, funding source (87%), professional opinion (76%), mental health consumer opinion (79%), and return of research results (91%) were believed to be important for considering study participation. Significantly more patients were willing to participate in a biobank managed by a university or clinic (78.2%) than one managed by government (63.4%) or industry (58.2%; both p < 0.001). The nine‐member community advisory board expressed interest in research to help predict the likelihood of bipolar disorder developing in a child of an affected parent and which medications to avoid. The advisory board endorsed the use of a comprehension questionnaire to evaluate participants' understanding of the study (e.g., longevity of DNA specimens, right to remove samples, accessing medical records) as a means to strengthen the informed consent process. Conclusions These national survey and community advisory data support the merit of establishing a biobank to enable studies of disease risk, provided that health records and research results are adequately protected. The goals of earlier diagnosis and individualized treatment of bipolar disorder were endorsed.